Possible involvement of oxytocin in modulating the stress response in lactating dairy cows - Sutherland, Mhairi A.; Tops, Mattie (Frontiers in Psychology, 2014)
Oxytocin can attenuate the physiological and behavioral response to stress in animals. In this study we investigated the relationship between plasma oxytocin concentrations and the behavioral and physiological response of dairy cows to a repeated psychological stressor (novel environment). Twenty lactating multi-parous dairy cows were milked in a familiar milking parlor and in a novel environment. Blood samples were collected before and after milking in the familiar parlor (baseline) and on the second and fifth day in the novel parlor to measure plasma cortisol and oxytocin concentrations. Heart rate was recorded on all cows during milking in the familiar and novel environment. On all test days, the behavioral response of cows to milk cluster attachment was scored. On day 2 in the novel parlor, the oxytocin response, cortisol concentrations and heart rate were greater, and heart rate variability was lower than baseline values recorded in the familiar parlor. The results from this study suggest that oxytocin release is increased in response to exposure to a psychological stressor (novel environment) and that cows adapt to this stressor over time. After initial suppression, oxytocin levels increased over days of milking in a novel environment, whereas indicators of stress simultaneously decreased. Furthermore, the oxytocin increase was associated with habituation of the cortisol response in anticipation of milking in a novel environment, suggesting that oxytocin may be involved in habituation to a novel environment in dairy cows. This mechanism of habituation to novel environments may reflect an association between oxytocin and a “familiarization-habituation response” to repeated exposure to an initially novel environment that has previously been reported in humans.